Behavior study of Bifidobacterium longum using solid state fermentation from commercial soybean meal - Rodríguez de Olmos, Antonieta (2021)
The development of alternatives to dairy products has gained great importance using plant-based foods. In this study, efforts have been made to develop vegetable alternatives from soybean paste without any supplement using single potential probiotic culture. Commercial soybean meal was inoculated with Bifidobacterium (B.) longum under previously fitted fermentation conditions by experimental design. Carbohydrates, organic acids, isoflavones, and amino acids profiles were studied in nine conditions of moisture and temperature, and also at several times in optimized conditions. Kinetics and technological parameters, effect of simulated gastric conditions on bacterium survival in optimized soybean paste, and their relationship with soybean matrix using scanning electron microscopy (SEM) were also evaluated. B. longum was able to use the main carbohydrates in soybean producing organic acids as was expected (acetic/lactic ∼ 1.5) and to enhance bioactive isoflavones (maximum concentration: 32.6 mg/50 g of soybean paste). Furthermore, B. longum showed high tolerance at simulated saliva solution and gastric juice, but the pancreatic solution deeply affected its viability in MRSs and also in soybean paste. Soybean paste represents an excellent vegetable candidate to be used as potential probiotic carrier food for B. longum and an attractive alternative to develop new functional foods.